Women and Law in Malawi: The experiences of women seeking child maintenance at Lilongwe Child Justice Court - Phiri, Limbani Zakeyo (University of Western Cape, 2020)
Magister Artium - MA === Malawi is endowed with a progressive, transformative and comprehensive legal and policy framework that guarantees the promotion and protection of human rights and justice for its citizenry, including women. The country is a party to multilateral human rights conventions, treaties, and protocols that strive to nurture and safeguard a culture that protects marginalised groups and has, thus, enacted relevant laws to domesticate the instruments. However, studies have shown that the legislative framework has not translated into practice that can create meaningful impact on the lives of ordinary citizens. My study explored the experiences of women that seek child maintenance through the Lilongwe Child Justice Court in Malawi.